Kondisi Kritis Keaslian Laras Slendro Banyumas - Mukhlis Anton Nugroho (Universitas Gadjah Mada, 2017)
Slendro is one kind of tuning music system exists in Banyumas. The characteristic of Slendro Banyumas is different from the existed Slendro in Surakarta, to Banyuwangi Slendro, Sundanese Salendro, ect. Slendro’s character is able to be detected from the interval pattern between of its tones. This is appropriate to the theoretical concept about laras that explain “one of the musical atmosphere defi ned by the tuning system which focuses on the jangkah pattern (interval) for its tones in one cycle”. This article aims toshow about the condition of Slendro Banyumas, nowadays, it is experiencing a shift due to the infl uence of the other tones. Slendro Banyumas threaten its authenticity.